2014
DOI: 10.1513/annalsats.201401-001ps
|View full text |Cite
|
Sign up to set email alerts
|

Can We Optimize Long-Term Outcomes in Acute Respiratory Distress Syndrome by Targeting Normoxemia?

Abstract: Since its original description in 1967, acute respiratory distress syndrome (ARDS) has been recognized as a devastating condition associated with significant morbidity and mortality. Advances in critical care medicine and ARDS management have led to a substantial increase in the number of ARDS survivors. Longterm cognitive impairment after critical illness is a significant public health concern. ARDS survivors frequently experience long-term cognitive impairment, as well as physical impairment, psychiatric mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Despite this guideline being published, several questions remain unanswered. Most importantly, how will oxygenation targets of strict normoxaemia vs low normoxaemia affect short‐ and long‐term patient‐important outcomes in patients admitted to the ICU, and in those with hypoxaemic respiratory failure? The HOT‐ICU trial aims to answer these important questions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this guideline being published, several questions remain unanswered. Most importantly, how will oxygenation targets of strict normoxaemia vs low normoxaemia affect short‐ and long‐term patient‐important outcomes in patients admitted to the ICU, and in those with hypoxaemic respiratory failure? The HOT‐ICU trial aims to answer these important questions.…”
Section: Discussionmentioning
confidence: 99%
“…However, ARDS survivors can show long-term cognitive dysfunction in terms of attention, memory, mental processing speed, and executive function. 24,51 In 1999, Hopkins et al 51 found marked cognitive impairment in all 55 ARDS subjects within their cohort at hospital discharge; at 2 y, 47% of survivors showed persistent neurocognitive impairment with no improvement from 1 to 2 y. More recently, Mikkelsen et al 24 confirmed that long-term cognitive impairment, especially in executive dysfunction, was present in 55% of survivors at 1 y. Cognitive impairment was significantly associated with lower oxygenation at 1 y and with psychiatric disorder, particularly anxiety.…”
Section: Neuropsychological Disabilitymentioning
confidence: 99%
“…Brain damage during Extracorporeal Life Support (ECLS) includes: neurocognitive impairment in survived patients, global brain injury and focal brain injury. Neurocognitive impairment in survivors from ARDS is of high concern, as many studies showed high rate of cognitive decline in this subset of patients (6)(7)(8). The authors, on the basis of correlation between hypoxemia and neurocognitive sequelae, hypothesized that the cerebral hypoxia might explain this phenomenon.…”
mentioning
confidence: 99%